A comparative study of the in-vitro dissolution profiles of paracetamol and caffeine combination in different formulations using HPLC - M.E.M. Hassouna, Y.M. Issa, A.G. Zayed (Journal of Applied Pharmaceutical Science)
Dissolution testing is an in vitro technique of great importance in formulation and development of pharmaceutical dosage forms, as it can be used as a substitute for in vivo studies under strictly defined and specified conditions. The main objective of the present study is to conduct the comparative dissolution studies of various brands of same dosage forms and treatment of obtained dissolution data by using ƒ2 to determine whether all the formulations used were equivalent or significantly different. Five different brands of drug containing paracetamol and caffeine from different manufacturers were used in the study, and dissolution testing in different dissolution media viz., water, 0.1 N HCl, phosphate buffer of pH 4.5 and phosphate buffer of pH 6.8 was conducted for 12 tablets from each brand for 60 min. by using dissolution testing apparatus USP type-II. Samples were withdrawn at 10 min. time interval and analyzed for drug content by using HPLC technique. Percent drug release at each time interval was calculated for tablets and the data obtained were treated with statistical technique to meet the FDA requirements for obtaining a waiver of bioavailability and bioequivalence studies.
Keywords: acetaminophen (paracetamol), caffeine, comparative studies of in-vitro dissolution, HPLC.